A peptide isolated from Hippocampus abdominalis improves exercise performance and exerts anti-fatigue effects via AMPK/PGC-1α pathway in mice. (October 2019) - Zhang, Yuanyuan; Ryu, Bomi; Cui, Yuhua; Li, Chengyong; Zhou, Chunxia; Hong, Pengzhi; Lee, Beajin; Qian, Zhong-Ji
Graphical abstract: Highlights: A peptide, LEDPFDKDDWDNWKS, was isolated from Hippocampus abdominalis . The peptide could prolong running time of mice. The peptide alter the expression of various biomarkers and reduce the accumulation of lactate. The peptide improved mitochondrial function and protected muscle fibers. Abstract: Seahorse is been used as a traditional Chinese medicine and invigorant for many years. Among, the seahorse is considered to have anti-fatigue effects. However, few researches have demonstrated such an effect. This study, the anti-fatigue effect of a novel peptide purified (SH200) from the seahorse ( Hippocampus abdominalis ) was investigated in C57BL/6 mice. The effect of SH200 on exercise performance was assessed using a Rotarod test and clinical biochemical parameters. In addition, the expression levels of muscular-associated proteins were examined by western blot and immunohistochemical analysis. The results revealed that SH200 prolonged the running time of mice, reduced the expression of creatine, CK, LDH, l -lactate, Citrate, and increased the production serum glucose and FFA, hepatic glycogen, ATP, and SDH. Addition, SH200 also improved mitochondrial function and protected muscle fibers via AMMPK/PGC-1α signal pathway. Thus, the SH200 is a potential candidate natural agent that could be used to reduce physical fatigue.